Trije vidiki javnega delovanja slovenske skupnosti v Italiji ob osamosvajanju Slovenije - Devetak, Robert (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
The Slovene community in Italy paid the utmost attention to the events in Slovenia at the time of the declaration of independence in June 1991 and the subsequent attack of the Yugoslav People’s Army. Drawing from newspaper reports, the article focuses on some major public events, charities and youth activities that were the result of cooperative activities of the Slovene community in Italy during the events in Slovenia. Thereby, the Slovene minority tried to influence the decisions of the Italian and European political leaders to intervene in the event of military aggression and support Slovenia’s independence, while also involving the public and successfully encouraging it to participate en masse in public events and charity campaigns to help Slovenia.
Keywords: Aid to Slovenia ’91; Crisis Unit in Aid of Slovenia; Krizni štab za pomoč Sloveniji; osamosvojitev Slovenije; osamosvojitvena vojna; Pomoč Sloveniji ’91; Slovenci v Italiji; Slovenes in Italy; Slovenia’s independence; war of independence